2007
DOI: 10.5194/acpd-7-10343-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation and characteristics of ions and charged aerosol particles in a native Australian Eucalypt forest

Abstract: Abstract. Biogenic aerosol formation is likely to contribute significantly to the global aerosol load. In recent years, new-particle formation (NPF) has been observed in various ecosystems around the world but hardly any measurements have taken place in the terrestrial Southern Hemisphere. Here, we report the first results of atmospheric ion and charged particle concentrations as well as of NPF in a Eucalypt forest in Tumbarumba, South-East Australia, from July 2005 to October 2006. The measurements were carri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 35 publications
4
40
1
4
Order By: Relevance
“…Charged particles displayed a narrow concentration band, or mode, centered close to 1 nm throughout the tropospheric column. A similar cluster ion pool has been observed in practically all ground-based measurements made so far Vartiainen et al, 2007;Suni et al, 2008;Venzac et al, 2007), reflecting the fact that small ion clusters are being continually formed in the atmosphere. Another mode of charged particles can be distinguished at sizes above roughly 20 nm.…”
Section: Cluster Size Distributions and Implications For Nucleationmentioning
confidence: 57%
“…Charged particles displayed a narrow concentration band, or mode, centered close to 1 nm throughout the tropospheric column. A similar cluster ion pool has been observed in practically all ground-based measurements made so far Vartiainen et al, 2007;Suni et al, 2008;Venzac et al, 2007), reflecting the fact that small ion clusters are being continually formed in the atmosphere. Another mode of charged particles can be distinguished at sizes above roughly 20 nm.…”
Section: Cluster Size Distributions and Implications For Nucleationmentioning
confidence: 57%
“…Compared to the aerosol distributions known from moderate climates in the Northern Hemisphere, the ultrafine particles in Western Australia behaved totally differently. In our study, nucleation mode particles were never observed over the natural vegetation, although the eucalyptus trees are considered to emit aerosol precursor compounds like isoprene (Suni et al, 2008). Instead, all ultrafines below 10 nm were found exclusively over the agricultural land.…”
Section: Resultsmentioning
confidence: 80%
“…Local enhancements were occasionally observed in coastal areas, but, for the analysis of particle distributions they were considered to be unimportant (Bigg et al, 1984). However, higher numbers of ultrafine particles are now also found in several other locations with high biogenic nucleation mode aerosol precursors emissions above and downwind of tropical forests on the Australian east coast (Suni et al, 2008;Guo et al, 2008). Ultrafine particles observed in high numbers off the Queensland coastline resulted from emissions from the Great Barrier Reef although with different chemistry compared to the Irish coastline at Mace Head (Saiz-Lopez et al, 2005, O'Dowd et al, 2007, Modini et al, 2009 The rationale for this project was to investigate the processes behind the regional change of the precipitation patterns in Western Australia (Sadler et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Just during the intensive part of the campaign nucleation events were observed on 4 out of 7 days. More details on the frequencies and types of nucleation events observed at this site were presented previously by Suni et al (2008). Figure 1 shows the particle size distribution measured with an SMPS (5-168 nm) during the nucleation events, while Fig.…”
Section: Observation Of Nucleation Eventsmentioning
confidence: 99%